Manipulating the Crystallization and Phase Transition for High‐Performance CsPbI2Br Solar Cells. Issue 6 (23rd December 2022) - Shan, Shiqi; Xu, Chang; Wu, Haotian; Niu, Benfang; Fu, Weifei; Zuo, Lijian; Chen, Hongzheng
Abstract: The inorganic perovskite solar cells (IPSC) are promising in the context of simultaneously delivering high efficiency and good stability. Developing a high‐performance and larger band gap IPSC is particularly in demand for commercialization due to their suitability to match with the prevailing silicon solar cells for tandem devices, while this is hindered by the poor morphology and phase stability of inorganic perovskite films. To address this issue, this work develops a combined method of nonstoichiometric composition and post‐cation exchange to improve the morphology and phase stability of the CsPbI2 Br IPSCs, and achieves a record efficiency of 17.80%. This work finds that excessive PbI2 regulates the CsPbI2 Br film crystallization, and thus, a high‐quality perovskite film with enlarged grains is obtained. Further depositing the formamidinium iodide on top of the CsPbI2 Br perovskite induces cation exchange during the post‐annealing process, which increases the phase stability of the perovskite film and significantly improves the device efficiency and stability. Therefore, this work provides an avenue toward high‐performance IPSCs, via the nonstoichiometric and ion exchange method. Abstract : High‐performance CsPbI2 Br inorganic perovskite solar cells (IPSC) with enhanced phase stability are demonstrated. A nonstoichiometric compositional engineering method is developed to quickly obtain high‐quality perovskite films with micrometer‐scale crystal grains. Moreover, a post‐cation exchange method is demonstrated to further enhance the efficiency and phase stability of CsPbI2 Br IPSCs, and enables a record efficiency of 17.80%.